Rural Wellbeing in Poland – Subjective Perspective - Agnieszka WOJEWÓDZKA-WIEWIÓRSKA; Hanna DUDEK (Communications of International Proceedings, 2023)
The paper focuses on the issue of subjective wellbeing in rural areas in Poland. In the analysis 2004-2018 data from the European Social Survey (ESS) were used. The issue of the wellbeing of the rural population in the context of the vitality and development of rural areas is crucial, both from research and from a practical point of view. The aim of the research was to identify the level and changes in wellbeing in rural areas in Poland. The territorial aspect of wellbeing was taken into account, comparing the level of life satisfaction and happiness of rural residents to other types of (urban) areas. It was found that there was a definite improvement in subjective wellbeing in rural areas in Poland. Residents of rural areas are more satisfied with their life than residents of towns and cities, but they are slightly less happy than residents of cities. Moreover, women rate their wellbeing better than men. The results of the research revealed the great importance of the spatial context in explaining the subjective aspect of wellbeing.
Keywords: rural areas; rural population; wellbeing; satisfaction with life